Análise da estratégia de atuação da ONG Luta pela paz na busca da inserção de jovens no mercado de trabalho - Amaral, Maria José Caetano do (2022)
This dissertation reflect son the worko fthe NGO “Luta pela Paz” in the transformation and social inclusion oflow-income populations, focus ingespecially on theem ployability of Young adults from the Nova Holanda community, located in the Complexo da Maré, Rio de Janeiro.The importance ofthe topic lies in know in ghowan NGO, located in a territory marked byviolenceand discrimination, and facing the scarce supply of work in relation to the high demand, especially from Young adults, offers support for the irinsertion with in the labor market. It is believed that Luta pela Paz's social initiatives are relevant toour society and to this specific area, given the lackof effective public policies from the state Government. The positive and negative aspect softh is activity will be presented, especially in terms of meeting the expectations of these young adults in terms ofaccess in gemployability.There search will address how the institution manages the interaction between private companie sand Young adults in the insertion of the labor market, in a scenario where most of these population from the outskirts of the city face many difficulties, such as lowschooling, earlyparenthood, day-to-day living with violence. These factors, addedto others, affect the possibility of employability, increasing in formality, under employment, pointing to higherun employment rates. In addition to accurate actions by actors from other institution saimingat social transformation of these Young adults and their respective families. There search will be develope dusing quantitative and qualitative variables, from interviews carried out through te “google forms” application with people involved with the project.A literature review will be present eedto serve as a basis to consubstantiate the case and a subsequente discussion of results.The purpose is to develop a critical reflection on the actions of the NGO "Luta por Paz" and other institutions with in a space of economic and political dispute (dominant groups), but at the same time, in a place of cultural, historic a land social relevance. The research process was carried out with the consente of all actors in this research.